The impact of agricultural fertilizers and pests on agricultural wealth in pine forests - Sharoot, Mustafa; AbdulKarim, Alrabab Tariq; Hamzah, Alaa Halos (Technium BioChemMed, 2025)
Reduced water quality, increased erosion, and the loss of vital animal habitat are all consequences of overfishing. Furthermore, the use of pesticides and herbicides during the wood harvesting process might harm non-target species and contribute to the loss of biodiversity. The health of the forests in the Southeast of the United States is also threatened by invasive pests and illnesses like the southern pine beetle and emerald ash borer. The loss of biodiversity and general health of forests can result from these pests' severe effects on forest ecosystems. Diseases and invasive pests can have a financial impact by devaluing forest products like wood. To address threats to the health of the forests in the Southeast region of the United States, several federal, state, and municipal policies and initiatives have been implemented. By lowering air and water pollutants that may damage forests, the Clean Air Act and the Clean Water Act are two federal laws that have had a major influence on the health of forests. Furthermore, threatened species that rely on forest ecosystems are safeguarded under the Endangered Species Act. The state's forest resources are under the Georgia Forestry Commission's care and protection. The Commission offers landowners technical support and direction on sustainable forestry techniques, as well as programs for pest control and forest health monitoring. One program that has been effective in encouraging sustainable forestry practices in the Southeast of the US is the Forest Stewardship Initiative. The program offers landowners who wish to use sustainable forestry methods on their property a number of advantages. One of the main advantages of the forest management program is that it offers landowners technical help. Advice on preserving animal habitat, planting and maintaining trees, and stopping soil erosion are a few examples of this assistance. Additionally, landowners can receive guidance on obtaining and preserving sustainable forestry accreditation. Along with technical support, the program offers financial incentives to landowners that adopt sustainable forestry.